IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PENGEMBANGAN PARIWISATA PANTAI SELATBARU KABUPATEN BENGKALIS - Berkahti, Shintarani; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Implementation of government policies Department of Tourism Culture Youth and Sports Bengkalis in the development of nautical tourism , there are several policies which are less effective and efficient so that the beach Selatbaru Not widely known outside the community and infrastructure conditions in Turkish Selatbaru very minimal . Based on data from the Department of Tourism Bengkalis Restra marine tourism development has been set based on a matrix of four kawasan.perumusan the subject matter of this research is how the implementation of development programs Bengkalis Selatbaru coast , so the purpose of this study was to determine how the development of nautical tourism conducted by the Department of Tourism .This research is a qualitative descriptive method . This research was conducted through observation, in-depth interviews and documentation . And data analysis techniques performed by illustrating and describing and grouping the data according to the type of data . The results of this study indicate that the efforts made by the Department of Tourism Bengkalis in the field of optimal development of nautical tourism have not been able to explore the potential and manage coastal selabaru so no levy generated by Selatbaru beach in revenue accounted Bengkalis .Keywords : Implementation of policy , government , development , beach Selatba